ANALISIS TINGKAT KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUSKESMAS DI KOTA BANDUNG - Tim Peneliti STIA LAN (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2007)
The research focuses on the delivery of public service at Bandung City Community Health Centres (Puskesmas). The choice of this locus is based on the assumption that Puskesmas as health centres provided by Bandung City Local Government is close to the community. In addition, Puskesmas is regarded affordable for poor people. General assumptions put on view that the Puskesmas’ health service delivery has yet to improve because a lot of complaints have been addressed by the clients (users) regarding their service delivery. However, the research result shows the opposite – the clients’ reflection on Bandung City Puskesmas’ health service delivery through questionnaires is generally good although some aspectsstill need improvement.